2020
DOI: 10.1007/s00277-020-04266-1
|View full text |Cite|
|
Sign up to set email alerts
|

Eltrombopag is effective in patients with relapse/refractory aplastic anemia—report from a single center in China

Abstract: Eltrombopag has shown a promising effect on patients with refractory/relapsed aplastic anemia (AA). However, data in Asian patients are limited due to the short launching time. Data from relapsed/refractory AA patients treated with eltrombopag in Peking Union Medical College Hospital from December 2017 to May 2019 were analyzed retrospectively. Totally 41 patients including 37 non-severe AA and 4 severe AA were analyzed with a median age of 47 (13~81) years old. The dosage of eltrombopag varies from 25 mg ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…The correlation between the absolute reticulocyte count and the ORR was also reported in a study on EPAG + ATG+CsA for newly diagnosed SAA patients [ 23 ]. For the EPAG monotherapy group, no influencing factors of the response rate were found, which was consistent with Ruan et al’s study [ 10 ]. Our study did not detect predictors for relapse events in either therapy group, which could be explained by the limited number of relapsed patients, which increased the difficulty of detecting significant differences.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The correlation between the absolute reticulocyte count and the ORR was also reported in a study on EPAG + ATG+CsA for newly diagnosed SAA patients [ 23 ]. For the EPAG monotherapy group, no influencing factors of the response rate were found, which was consistent with Ruan et al’s study [ 10 ]. Our study did not detect predictors for relapse events in either therapy group, which could be explained by the limited number of relapsed patients, which increased the difficulty of detecting significant differences.…”
Section: Discussionsupporting
confidence: 91%
“…The AE rate of EPAG+tacrolimus in patients with refractory/relapsed AA was 20% to 30%, which was lower than the AE rate reported in previous studies on EPAG monotherapy for relapsed/refractory AA patients [ 17 , 22 ]. The most common AEs in the EPAG+tacrolimus group and EPAG monotherapy group included dyspepsia and skin pruritus, which were generally consistent with the AEs reported in other studies [ 10 , 16 ], and no severe AEs of CTCAE grades 3-4 were observed.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations